PENGARUH TERAPI RELAKSASI BENSON DAN AUTOGENIK TERHADAP PENURUNAN KECEMASAN PASIEN HIPERTENSI - Puling, Dwi M; sutrisno, sutrisno (LPPM STIKes SATRIA BHAKTI NGANJUK, 2023)
One of the psychological aspects of health problems that arise due to hypertension is anxiety. This problem can have an impact on physical disorders or cause a worse disease prognosis. The purpose of this study was to determine the effect of beson and autogenic relaxation therapy on reducing anxiety in hypertensive patients. The research design used a pre-experimental method with a one group pre-test and post-test design approach. This research was conducted in the working area of the Pukesmas Blowerti Kota Kediri, using a porposive sampling technique to obtain a total of 20 respondents. Data were collected using the HARS questionnaire sheet, and using the Wilxocon analysis test.